1999
DOI: 10.1142/s0218194099000309
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining for Predictors of Software Quality

Abstract: Knowledge discovery in data bases" (KDD) for software engineering is a process for finding useful information in the large volumes of data that are a byproduct of software development, such as data bases for configuration management and for problem reporting. This paper presents guidelines for extracting innovative process metrics from these commonly available data bases. This paper also adapts the Classification And Regression Trees algorithm, CART, to the KDD process for software engineering data. To our kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…They also argued that change data is a better predictor of defects than code metrics in general. Studies by Arisholm and Briand [21] and Khoshgoftaar et al [22] also reported that prior changes are a good predictor of defects in a file. Hassan [3] used the complexity of a code change to predict defects.…”
Section: Using Process Metricsmentioning
confidence: 95%
“…They also argued that change data is a better predictor of defects than code metrics in general. Studies by Arisholm and Briand [21] and Khoshgoftaar et al [22] also reported that prior changes are a good predictor of defects in a file. Hassan [3] used the complexity of a code change to predict defects.…”
Section: Using Process Metricsmentioning
confidence: 95%
“…Component dependencies can be used to compute relevant quality measures of software repositories, for instance to identify particularly fragile components [7,13,15]. It is well known that small-world networks are resilient to random failures but particularly weak in the presence of attacks, due to the existence of highly connected hub nodes [2].…”
Section: Strong Dependenciesmentioning
confidence: 99%
“…And, this method is also useful in decreasing the number of bugs made by maintainers who are not aware of implicit coding rules. In addition, this method it very powerful in practical use because it can directly detect the line number of faulty code area with detailed instructions, while previous methods for predicting fault-prone modules using software metrics only say which modules are faulty [4,7].…”
Section: Introductionmentioning
confidence: 99%